Analisis Tokoh Utama dalam Film Miracle In Cell No 7 : Sebuah Kajian Psikoanalisis Jacques Lacan - Mhd Syafiq Andika; Muhammad Surip (BLAZE : Jurnal Bahasa dan Sastra dalam Pendidikan Linguistik dan Pengembangan, 2024)
Describing real, imaginary, and symbolic analysis in Miracle in Cell No. 7 using Jacques Lacan's psychoanalytic theory was the goal of this research. The research method used is qualitative descriptive. The instrument used is the documentation of the film. Data collection techniques are used to study libraries, recording and recording techniques that cover scenes, clips, durations, and setting aspects. Data analysis techniques are performed consisting of reducing data that emerges from the records of research objects, displaying data in the form of narratives, and verification by drawing conclusions. The results of the research showed that in the real phase, the visible protagonist showed deep affection for his daughter, depicting a warm father-child relationship. The imaginary phase, which marks the child's self-identification process through the mirror phase where unfulfilled desires can lead to a feeling of separation from parents that shows the great hope of parents for their daughters to be successful and happy. This dream shows Dodo's great desire for his family and the imaginative attraction to find meaning and purpose in a difficult life.